Optimizing dengue surveillance with ‘Tunggal Dara’ android-based application: key findings for sustainable implementation - Amalia, Ichlasul; Ahmad, Riris Andono; Lazuardi, Lutfan (Universitas Gadjah Mada, 2023)
Purpose: This study evaluated the effectiveness of 'Tunggal Dara,' an Android-based system, in optimizing dengue surveillance in Semarang, Indonesia, using the Modified Consolidated Framework of Implementation Research (mCFIR). Methods: This explanatory mixed-method study utilized an online mCFIR questionnaire to measure performance and importance scores across five domains and two sub-domains. Perspectives of 46 epidemiologists and 167 community health workers (CHWs) were included. Focus group discussions, key-informant interviews with relevant stakeholders at the local-national level, field observations, and application log analysis were also conducted. Descriptive and thematic analyses were performed to provide insights into its fidelity, penetration, and sustainability. Results: In 2022, the weekly participation rate remained stable, ranging from 76.3-97.7% for village-level CHWs and 100% for epidemiologists, indicating strong program sustainability. However, cadres and epidemiologists rated performance support from the outer setting domain as the lowest, recognizing its potential impact when executed properly. Three major themes emerged as facilitators: solid community engagement, high users’ demand and commitment, and collaboration opportunities. Four key barriers were discovered: integration and interoperability challenges, data input quality and standardization issues, variations in end-user characteristics, and limited involvement of local stakeholders. Conclusion: This study has the potential to contribute significantly to the field of dengue surveillance in Indonesia and beyond, providing valuable insights into the benefits and limitations of adopting digital innovations to combat this persistent public health threat.